Exploring the Clinical Features and Treatment Outcomes of Autoimmune Encephalitis in Pediatric Patients: A Cross-Sectional Analysis - Ali, Rabia; Khan, Muhammad Saad; Khalid, Usama; Mahmood, Khalid; Raza, Afrina (Indus Journal of Bioscience Research, 2025)
Background: Autoimmune encephalitis is an increasingly recognized cause of acute neurological dysfunction in children and can present with a wide spectrum of neuropsychiatric and neurological symptoms. Prompt diagnosis and treatment are important for favourable outcomes, especially in resource constrained settings. Objectives: This study was an objective to explore the clinical features, diagnostic profiles and treatment outcomes of pediatric patients with autoimmune encephalitis in a tertiary care hospital in Lahore, Pakistan. Methods: It is a cross sectional study that was carried out at a tertiary care hospital in Karachi from January to December 2024. A total of 52 children aged 1 to 18 years with confirmed autoimmune encephalitis were included. Clinical presentations, antibody subtype, neuroimaging, cerebrospinal fluid (CSF) analysis, treatment, and outcome at discharge and at three months clinic follow up were recorded. Results: Behavioral changes (76.9%), seizures (69.2%), altered consciousness (61.5%), and other (45.7%) were the most common presenting symptoms. The most frequent subtype was anti-NMDAR encephalitis (61.5%). EEG abnormalities were found in 80.8%, and pleocytosis in the CSF 67.3%. Corticosteroids were given to all patients and 76.9% received IVIG, 28.8% underwent plasmapheresis. Indeed, by three months, 80.8 percent of patients had full or nearly complete recovery, and 7.7 percent relapsed. Improved outcomes (p = 0.03) correlated with early initiation of immunotherapy. Conclusion: The range of symptoms seen with pediatric autoimmune encephalitis can make this entity a challenge to recognize, treat promptly, and mitigate the morbidity caused by this illness. An early diagnosis followed by aggressive immunotherapy is associated with favorable outcomes and demands heightened clinical awareness with standardization of management protocols.